Numerical analysis on thermal performanace of staggered pin-fin assembly - Ibrahim, Kamarulzaman (2007)
Steady state heat transfer and friction characteristics and performance analysis for flow through a rectangular channel with heat sinks of circular cross-section pin fins in turbulence flow was studied in the present study. The heat sink was immersed in the channel with fluid flowing at constant inlet temperature and pressure of uniform approach velocity approaching the pin fin at normal to pins. This study had investigate the performance of heat sinks numerically by modelling the model using mesh generator, GAMIT and analyzing the model using commercially available Computational Fluid Dynamic software, FLUENT. The study concentrated on pins with staggered arrangements with variations in the clearance above pins (C) to pin height (H), clearance ratio (C/H = 0.35, 1, 3, 7 and 15) and ratio of distance between pins to the pin diameter (Sx/d = 1, 1.5, 2, 2.5 and 3) along the streamwise direction while pin spacing along the spanwise direction was maintain fixed. Ascertainment of the performance of the model were by using the ratio of duct average Nusselt number for pinned model base on projected area ( Nu ) to the duct average Nusselt number of a smooth surface (Nus). The turbulence flow of Reynolds number 10000 – 50000 were modelled and simulated using the k-e modelling option of FLUENT. The comparatively lower Reynolds numbers of 10000 – 30000, lower interfin distance of Sx/d = 2 and clearance ratio should be a preferred staggered arrangement option.